Stirring the porphyrin alphabet soup functionalization reactions for porphyrins - SENGE, MATHIAS (My University, 2011)
Advances in the synthesis of unsymmetrically meso substituted porphyrins are based on the development of new total syntheses and porphyrin functionalization methods. These methods have replaced earlier mixed condensation reactions and give synthetic access to almost any desired meso-substituted porphyrin. They 10 include the complete series of porphyrin homologues and regioisomers of the Ax-series with either alkyl or aryl residues, and numerous examples of ABCD-type chromophores. The syntheses are based on a combination of classic functionalization reactions, the use of organolithium reagents in SNAr reactions, and organometallic reactions with Pd, Ni, Cr, Ru, B, and Sn catalysis. This feature article gives an account of our work in the past decade to develop synthetic methods for the Ax- and ABCD-type porphyrins and their use as 15 optical materials and photosensitizers
PUBLISHED
Keywords: Porphyrins